Inspiring Young Learners Toward a Career in Healthcare Using Simulation. Issue 6 (December 2020) - Yeh, Vicky J.-H.; Mukhtar, Fareeda; Rajesh, Aashish; Baloul, Mohamed S.; Chandra, Abhishek; Shaikh, Nizamuddin; Backstrom, Courtney; Rivera, Mariela; Asirvatham, Usha; de Azevedo, Rafael; Farley, David R.
Abstract : Summary Statement: To inspire young learners toward a career in healthcare and provide them opportunities to learn lifesaving skills, a hospital-based simulation center collaborated with a local middle school to develop a 88-minute simulation-based educational activity. The activity consisted of eight 10-minute stations on lifesaving and basic medical skills. One hundred fifty students participated. Evaluation surveys showed students favored stations with extensive hands-on activities and valued the opportunity to interact with health professionals. Students also reported more interest in science careers after the visit. This collaborative effort is time-efficient and low-budget simulation-based learning experience that had an immediate impact on middle school students. Abstract : Supplemental digital content is available in the text.